Sports Goods Foundation of India : A Case Study of a Solution Based NGO - Soni, Anchal; Verma, Rajesh; Joshi, Mahesh Chandra (Prabandhan: Indian Journal of Management, 2016)
The Indian sports goods industry is well-known in the entire world, with a size of approximately US$ 127.76 million in 2012-13, and the sports goods are mostly exported to U.K., U.S., and Australia. The Sports Goods Export Promotion Council (SGEPC), a Government of India sponsored organization is working for the promotion of India's exports of sports goods. Jalandhar is considered as the sports industrial hub and is the leading exporter of sports goods in Asia. Sports companies from Jalandhar have reputed buyers like Nike, Adidas, and associations like FIFA. Mid 1990-onwards, the sports goods manufacturing industry had a critical time as the industry was found to employ child labour for the production of inflatable balls. During the 1998 football World Cup, media coverage of child labour usage in football manufacture led to a boycott of the inflatable balls exported from India and Pakistan, and major clients like Nike, Adidas, Puma, and FIFA cancelled the orders of footballs. To eradicate the issue of child labour from the sports goods industry, the exporters of sport goods willingly came together and founded the Sports Goods Foundation of India (SGFI) with the involvement of 25 sports goods manufacturing companies. SGFI emerged as a solution based NGO, which is addressing the problems of the industry successfully. Various projects under SGFI are aimed to develop a self-imposed and reliable system to prevent child labour from the entire sports goods industry. SGFI took initiatives to withdraw children from hazardous working conditions in the football stitching industry by providing them with necessary education, skill training, health care, and social protection services.